Use of the somatostatin analogue octreotide to localise and manage somatostatin-producing tumours. Issue 6 (1st June 1998) - Angeletti, S; Corleto, V D; Schillaci, O; Marignani, M; Annibale, B; Moretti, A; Silecchia, G; Scopinaro, F; Basso, N; Bordi, C; Delle Fave, G
Abstract : Background —Somatostatin receptor scintigraphy (SRS) and octreotide therapy have both changed the management of gastroenteropancreatic endocrine tumours, but very few data are available on the use of SRS and octreotide to visualise and treat somatostatinomas. Method —The results of SRS and octreotide treatment in three somatostatinoma patients were examined. Results —SRS was able to detect extensive hepatic involvement in patient 1, one hepatic and one pancreatic lesion in patient 2, and one hepatic lesion in patient 3. Octreotide therapy (0.5 mg/day subcutaneously) was effective in decreasing plasma levels of somatostatin in all three patients. Symptoms (diabetes and diarrhoea) were greatly improved in the two patients with "somatostatinoma syndrome". Conclusion —The study shows that somatostatinoma, like most other gastroenteropancreatic endocrine tumours, possesses functioning somatostatin receptors.